A perspective on diuretic resistance in chronic congestive heart failure - Shah, Niel (Ther Adv Cardiovasc Dis, 2017)
Chronic congestive heart failure (CHF) is a complex disorder characterized by inability of the heart to keep up the demands on it, followed by the progressive pump failure and fluid accumulation. Although the loop diuretics are widely used in heart failure (HF) patients, both pharmacodynamic and pharmacokinetic alterations are thought to be responsible for diuretic resistance in these patients. Strategies to overcome diuretic resistance include sodium intake restriction, changes in diuretic dose and route of administration and sequential nephron diuretic therapy. In this review, we discuss the definition, prevalence, mechanism of development and management strategies of diuretic resistance in HF patients.